POSITIONS OF EURASIAN ECONOMIC UNION MEMBER STATES IN THE WORLD ECONOMY AT THE PRESENT STAGE - K. Bagdasaryan (Вестник университета, 2016)
Two years later after formation of the Eurasian economic union many European and American economists popularizing an image of the integration union as politized with weak dynamics of development and weak economic prospects. Firstly, not all member states of the Eurasian economic union are members of the World Trade Organization, secondly conditions of accession to the World Trade Organization of these states are different. There by the future of Eurasian economic union depends on many factors, including on consensus concerning the tariff charges, on intra- Eurasian economic union trade, on development and expansion of the domestic market, and also on behavior of external traders. An author analyses it on international level to show position of the Union in world economy. For the more objectiveness respectable international organizations such as World Bank, International Monetary Fund and World Trade Organization are chosen as the main sources of research.